Pengembangan Modul Matematika Berbasis Kontekstual Terintegrasi Ilmu Keislaman - Annisah Kurniati (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This study aims to analyze, describe the validity, and the practicalities of the development of mathematics modules integrated contextually based on Islamic science students. This type of research is the development of research (research and development / R & D). Subjects in the trial that high school students IT Az-Zuhra Islamic School. The study design using the ADDIE research model. As the name implies, the model ADDIE consists of five main phases or stages, namely (A) nalysis, (D) esign, (D) evelopment, (I) mplementation, and (E) valuation. Type of data collected in this study is primary data, i.e. data obtained directly from the questionnaire. Data collection instrument in the form of questionnaire test questionnaire validity and practicalities. Data were analyzed with descriptive analysis techniques. The results showed that the modules integrated mathematics contextually based Islamic science is valid and practical to use.